LGG-33. A 40-year cohort study of evolving hypothalamic dysfunction in 90 infants and young children (<3y) with optic pathway gliomas. (3rd June 2022) - Picariello, Stefania; Cerbone, Manuela; D'Arco, Felice; Gan, Hoong-Wei; O'Hare, Patricia; Aquilina, Kristian; Opocher, Enrico; Hargrave, Darren; Spoudeas, Helen Alexandra
Abstract: BACKGROUND: Despite high survival, paediatric optic pathway hypothalamic gliomas are associated with significant morbidity and late mortality. Those youngest at presentation have the worst outcomes. METHODS: We aimed to assess presenting disease, tumour location and treatment factors implicated in the evolution of neuroendocrine, metabolic and neuro-behavioural morbidity in children diagnosed before their 3rd birthday and followed over four decades (1981- 2020). RESULTS: Ninety infants/young children followed-up for 9.5 years (range 0.5-25.0) were included in the study. Fifty-two (57.8%) patients experienced endo-metabolic dysfunction (EMD), the large majority (46) had hypothalamic involvement (H+) and lower endocrine event free survival (EEFS) rates. Median time to first endocrine event was 3.4 years, with EEFS declining up to 13.6 years after diagnosis. EMD was greatly increased by a diencephalic syndrome presentation (85.2% vs 46%, p=0.001), H+ (OR 6.1 95% CI 1.7 – 21.7, p 0.005), radiotherapy (OR 16.2, 95% CI 1.7 – 158.6, p=0.017) and surgery (OR 4.8 95% CI 1.3- 17.2, p=0.015), all associated with anterior pituitary disorders. Obesity occurred in 25% of cases and clustered with the endocrinopathies. Posterior pituitary disorders were recorded in 15 subjects (16.7%), only after surgery and/or as a consequence of hydrocephalus in those with suprasellar tumours and hypothalamic disease. Neuro-behavioural deficits occurred in over half (52) of the cohort and were associated with H+ (OR 2.5 95% C.I. 1.1 – 5.9, p=0.043) and radiotherapy (OR 23.1 C.I. 2.9 – 182, p=0.003). CONCLUSIONS: Very young children with OPHG carry a high risk of endo-metabolic and neuro-behavioural comorbidities which deserve better understanding and timely/parallel support from diagnosis to improve outcomes. These evolve in a complex hierarchical pattern overtime whose aetiology appears predominantly determined by injury from the hypothalamic tumour location alongside adjuvant treatment strategies.